Facing the heat: initial probing of the City of Johannesburg's heat-health planning. Issue 2 (4th May 2019) - Nana, Manisha; Coetzer, Kaera; Vogel, Coleen
ABSTRACT: The City of Johannesburg (CoJ) will likely experience more frequent heat waves by 2100, the health impacts of which are being prioritized for strategic focus. We identified challenges and opportunities for better operationalizing heat wave considerations within the Environmental Health Department of the City of Johannesburg. By obtaining a deeper appreciation of the 'issues of concern' and existing 'contradictions', that is the context in which these practitioners are located, the opportunities and barriers to engagement, helps to surface the issues that may confront the City when planning for extreme heat and climate change adaptation in the future. Currently, heat waves are absent from the local Department's mandate, with unclear legislative requirements blurring the responsibility for heat wave planning. Service delivery backlogs relegate heat wave considerations, as do the Department's constituencies for whom heat waves are not yet of concern. However, heat wave planning supports community health education; raising public awareness of associated health risks and should be considered in future 'climate proofing' the City.